Diagnosis of Planetary Gearbox Crack Fault based on Torsional Vibration Signal Windowed RMS Time-domain Synchronous Averaging - Wei Wei; Yunpeng Li; Jingyuan Liang (Jixie chuandong, 2021)
Planetary gearboxes have the advantages of compact structure，high transmission efficiency，stable operation，etc.，and are widely used in heavy loads and key mechanical equipment. Since planetary gearbox often works in harsh environment，its key components are prone to tooth root crack fault damage and are not easy to be identified，easy to cause security risks. Compared with traditional transverse vibration signal，torsional vibration signal is not affected by the modulation of time-varying transmission path in theory，it has great advantages，so its frequency component is simple and it is easy to extract fault features. Taking torsional vibration signals as the analysis object，a windowed RMS time-domain synchronous averaging technique is proposed to realize the early tooth root crack fault diagnosis of planetary gearbox，and a fault simulation test bed is built to verify the effectiveness of the method.